Polysaccharides from Vaccaria segetalis seeds reduce urinary tract infections by inhibiting the adhesion and invasion abilities of uropathogenic Escherichia coli - Yao, Rongmei; Mao, Xin; Xu, Yingli; Qiu, Xue; Zhou, Lirun; Wang, Yaxin; Pang, Bo; Chen, Mengping; Cao, Shan; Bao, Lei; Bao, Yanyan; Guo, Shanshan; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The seeds of Vaccaria segetalis (Neck.) are from a traditional medicinal plant Garcke, also called Wang-Bu-Liu-Xing in China. According to the Chinese Pharmacopoeia, the seeds of V. segetalis can be used for treating urinary system diseases. This study was designed to investigate the underlying mechanism of VSP (polysaccharides from Vaccaria segetalis) against urinary tract infections caused by uropathogenic Escherichia coli (UPEC). Here, both in vitro and in vivo infection models were established with the UPEC strain CFT073. Bacterial adhesion and invasion into bladder epithelial cells were analyzed. We found that VSP reduced the adhesion of UPEC to the host by inhibiting the expression of bacterial hair follicle adhesion genes. VSP also reduced the invasion of UPEC by regulating the uroplakins and Toll-like receptors of host epithelial cells. In addition, the swarming motility and flagella-mediated motility genes flhC, flhD and Flic of UPEC were diminished after VSP intervention. Taken together, our findings reveal a possible mechanism by which VSP interferes with the adhesion and invasion of UPEC.